Pengaruh Electronic Word of Mouth di Media Sosial Instagram dan Atribut Produk Wisata terhadap Keputusan Berkunjung di Floating Market Lembang - Vegita Muflikhah,; Yustisia P. Mbulu; I Made Adhi Gunadi (Journal of Tourism Destination and Attraction, 2018)
Abstract Electronic word of mouth becomes an important place for the visitors to give their opinion about their experience, because when someone is doing electronic word of mouth, they will pay attention to the aspects of the tourism products that have became the experience in visiting a tourism object. This research attempts to identify electronic word of mouth on Instagram Floating Market Lembang’s social media, identify tourism product attributes in Floating Market Lembang, analyze influence of electronic word of mouth on Instagram social media and tourism product attributes towards tourist decision to visit Floating Market Lembang. The research design used is quantitative with multiple linear regression data analysis techniques. The results of this research have identified electronic word of mouth on Instagram social media and tourism product attributes in Floating Market Lembang, it was found that three electronic word of mouth variables consisting of intensity, valence of opinion and content significantly influence the decision variables visited at the Floating Market Lembang. While tourism product attributes found only one of three variables that significantly influence the decision variables visited in the Floating Market Lembang. One of these variables is tourism attraction, while the other two variables that do not influence the decision variables visited in Floating Market Lembang are amenities and accessibility.